On the formation of AlSi10Mg single tracks and layers in selective laser melting: microstructure and nano-mechanical properties - Aboulkhair, Nesma T.; Maskery, Ian; Tuck, Christopher; Ashcroft, Ian; Everitt, Nicola M. (Elsevier, 2016)
Selective laser melting (SLM) is a relatively new manufacturing technique that can be used to process a range of materials. Aluminum alloys are potential candidates for SLM but are more difficult to process than the titanium alloys more commonly used with this technique. This is because of the former’s physical properties that can result in high levels of porosity in the final parts. Although the majority of studies to date into the processing of Al alloys by SLM have considered the development of load bearing objects, in particular porosity reduction and mechanical characterization of the parts, it is also important to study the single tracks formed during the process. This paper studies the effect of changing the scan speed on the formation of fusion lines and single tracks from an Al alloy, as well as their overlap to form a single layer. The geometrical features of the melt pools as well as the boundaries of continuity and/or irregularities were defined and showed dependence on scan speed. Keyhole mode melting domination was observed. The scan tracks and layers were porosity-free suggesting pores to form with layer accumulation. Investigations showed that increasing the layer thickness should be avoided as it promoted defects. Energy dispersive X-ray (EDX) mapping was implemented to compare the chemical composition distribution in the SLM material and its as-cast counterpart. A fine microstructure with homogenous distribution of the alloying elements was observed. Nanoindentation and EDX were used to establish an understanding of the hardness profile across melt pools of single tracks and their interrelation to the chemical composition. The elemental distribution yielded uniform high nano-hardness with no spatial variation across the SLM material.